Photothermal-augmented reactive oxygen species oxidative synergistic therapy based on nanoceria doped mesoporous polydopamine nanoplatform. (January 2023) - Jiang, Suhua; Zhu, Fukai; Lin, Yang; Ran, Liu; Lin, Fulin; Tian, Haina; Hu, Ting; Wang, Peiyuan; Lu, Canzhong
Graphical abstract: Highlights: Nanoceria doped mesoporous polydopamine nanoplatform has been successfully fabricated. The nanotherapeutics have satisfactory photothermal conversion efficiency as ∼51.41%. Amplified ROS oxidative therapy was realized via the doped nanoceria. The combined treatments resulted in complete tumor cells eradication both in vitro and in vivo . Abstract: Owing to residual tumor tissues around the treatment margins, it is difficult to totally ablate large tumors, eliminate disseminated and metastatic nodules as well as prevent the tumor recurrence simultaneously by conventional photothermal therapy (PTT). In this work, PTT combined reactive oxygen species oxidative therapy (ROT) was conducted via mesoporous polydopamine nanosphere with nanoceria doping (MPDA-Ce). After surface anchoring with Arg-Gly-Asp (RGD) molecules, the dispersive stability and tumor targeting of this innovative nanoplatform were substantially boosted. In vitro studies revealed that the unique nanotherapeutics had satisfactory photothermal conversion efficiency (η = 51.41%), continuous nanoceria release in cytoplasm of tumor cells after acid microenvironment (pH = 5.5) induced biodegradation. Significantly, hyperthermia amplified the abundant reactive oxygen species generation under 808 nm laser irradiation that potent ROT was realized with only 27.1% cells alive. Strikingly, Indocyanine green (ICG) loaded MPDA-Ce with RGD modification shows robust tumor targeting capability in breast carcinoma bearing Balb/C mice under fluorescent imaging in the second near-infrared window. The combined treatments resulted in complete tumor cells eradication under 808 nm laser illumination both in vitro and in vivo . This work highlights the promising application of MPDA-Ce as a powerful nanoplatform for ROT and PTT combined treatment in clinical.